The effect of educational computer games on the academic resilience, academic self-regulation, and academic achievement of EFL students - Deng, Lin; Daverpanah, Nikoo; Izadpanah, Siros (Frontiers in Psychology, 2023)
Introduction In recent years there has been an increasing interest in the field of educational computer games (ECGs). Although ECGs have been researched, more analyses still need to be performed on these variables to check their effects on language learning. Methods To this end, 74-third grade female state high school students from two schools in Zanjan were selected through a two-stage cluster random sampling method. The number of students in each class was 37. One of the classes (control group) was trained traditionally and the other was for one semester through the researchers-made ECGs. After completing the training, the research tools were performed as a post-test on the experimental and control groups. The data collection stage took place for about 6 months. Results Based on the results from the research questions, the use of training computers has been effective in increasing AR, ASR, and AA. Discussion It has significant implications for teachers and learners in the EFL context and opens interesting opportunities for administrators and curriculum developers to explore when planning EFL courses.